Eating Right from 8 to 18 : - Nissenberg, Sandra K. (Wiley, 2001)
Help your child develop healthy eating habits that will last a lifetime Most children establish lifelong eating patterns between the ages of 8 and 18. This practical and authoritative guide is the ultimate resource for parents who want to help their children adopt and enjoy a diet that will keep them healthy, well nourished, and physically fit, both now and for the rest of their lives. Eating Right from 8 to 18 helps you educate your children about nutrition; steer them away from a constant diet of junk food and fast food; and provide them with delicious, nutritious meals that will appeal to even the pickiest eaters. You'll also find specific solutions to issues of special concern, such as eating disorders, chronic fad dieting, and more. In this reliable, comprehensive guide, you'll discover: Clear, easy-to-follow nutritional guidelines for children More than 100 delicious, nutritious, easy-to-prepare recipes What to do if your child is naturally underweight or overweight How to ensure that vegetarian children are getting enough protein Special nutritional guidelines for young athletes It is hard sometimes to know whether you're doing the right thing for your child. Using the proven solutions and techniques you'll find in Eating Right from 8 to 18, you can solve your child's eating-related problems with complete confidence.